The Influence of Environmental and Social Performance towards Cumulative Abnormal Returnon Listed Companies in Indonesia Stock Exchange - Indahsari, Lilis Nur; Widhianningrum, Purweni (Universitas Negeri Malang, 2018)
This research aims to determine the influence of environmental and social performance against the cumulative abnormal return on listed companies in Indonesia stock exchange. The type of this research is quantitative research. The population in this research are all listed companies in Indonesia stock exchange during the period of the year 2012-2015. Sampling techniques in this research using the technique of purposive sampling, so that obtained the number of samples as much as 11 companies. Data analysis techniques in this study using multiple regression analysis. The results of this research showed that the environment and social performance have significant impact on the cumulative abnormal return. This indicates that investors are more concerned about social performance because it’s related to the welfare of the community especially employees.